LEGAL ANALYSIS OF DEFAULT IN TERMS OF SERVICE QUALITY AND ITS IMPACT ON THE COMPANY AND EMPLOYEES COMPANY AND EMPLOYEES - Isna Zakiya; Basyarudin Basyarudin (CV. CAKRAWALA RISET, 2026)
Service quality is part of the company's legal obligations to consumers, so that non-compliance of services with predetermined standards can lead to defaults that have an impact on companies and employees. This study aims to analyze legally default in service quality and its impact on companies and employees with the object of research PT Lion Super Indo Tirtayasa Branch Bandar Lampung. The research method used is normative and empirical juridical approach in which normative studies are conducted through analysis of civil law provisions and consumer protection, while empirical studies are obtained through direct observation of researchers as employees of service practices, supervision, and handling of consumer complaints. The results show that the company places service quality as a top priority through the implementation of service standards, customer satisfaction surveys, and compensation mechanisms in the event of non-optimal service, but in practice there are still potential defaults stemming from employee performance and behavior. The default has an impact on the company in the form of legal risk, decreased consumer confidence, and reputational disruption, while for employees it has implications for internal sanctions and professional pressure. It can be concluded that service quality has a strong legal dimension and must be managed systematically. Recommendations from the research are the need to strengthen supervision, coaching, and understanding of the law for employees so that service quality is maintained and the risk of default can be minimized, so that the interests of consumers, companies, and employees can be protected. consumers, companies, and employees can be protected in a balanced manner